Einstein gravity with torsion induced by the scalar field - Ozcelik, H. T.; Kaya, R.; Hortacsu, M. (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2018)
We couple a conformal scalar field in (2+1) dimensions to Einstein gravity with torsion. The field equations are obtained by a variational principle. We could not solve the Einstein and Cartan equations analytically. These equations are solved numerically with 4th order Runge-Kutta method. From the numerical solution, we make an ansatz for the rotation parameter in the proposed metric, which gives an analytical solution for the scalar field for asymptotic regions. (C) 2018 Elsevier Inc. All rights reserved.
Keywords: Torsion; Coupled to scalar; Solutions with torsion; GENERAL-RELATIVITY; COSMOLOGICAL CONSTANT; 2+1 DIMENSIONS; BLACK-HOLE; SPACE-TIME; CARTAN; SUPERNOVAE; SPIN; Physics